∫ 0 1 x sin ( tan − 1 x ) cos 2 ( tan − 1 x ) + 4 x 2 d x
The integral shown above can be written as A − B π , where A and B are integers. Find the value of A + B .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I did exactly same!!!
It is important to note that:
sin ( tan − 1 x ) = x 2 + 1 x and cos ( tan − 1 x ) = x 2 + 1 1
So:
∫ 0 1 x sin ( tan − 1 x ) cos 2 ( tan − 1 x ) + 4 x 2 d x
= ∫ 0 1 x x 2 + 1 x x 2 + 1 1 + 4 x 2
= ∫ 0 1 x 2 + 1 1 1 + 4 x 2 + 4 x 4 d x
= ∫ 0 1 x 2 + 1 1 ( 1 + 2 x 2 ) 2 d x
= ∫ 0 1 x 2 + 1 2 x 2 + 1 d x
= ∫ 0 1 2 − x 2 + 1 1 d x
= 2 − arctan ( x ) ∣ ∣ ∣ ∣ ∣ 0 1
= 2 − 4 π
Then:
A = 2 , B = 4 , A + B = 6
Problem Loading...
Note Loading...
Set Loading...
cos ( tan − 1 x ) sin ( tan − 1 x ) = tan ( tan − 1 x ) = x , x sin ( tan − 1 x ) = cos ( tan − 1 x ) 1 − cos 2 ( tan − 1 x ) = x 2 cos 2 ( tan − 1 x ) cos 2 ( tan − 1 x ) = 1 + x 2 1 ⇒ cos 2 ( tan − 1 x ) d x = 1 + x 2 d x l e t y = tan − 1 ( x ) , t h e n d y = 1 + x 2 d x = cos 2 ( tan − 1 x ) d x I = ∫ 0 1 x sin ( tan − 1 x ) cos 2 ( tan − 1 x ) + 4 x 2 d x = ∫ 0 1 cos ( tan − 1 x ) cos 2 ( tan − 1 x ) + 4 x 2 d x = ∫ tan − 1 0 tan − 1 1 cos ( y ) cos 2 ( y ) + 4 tan 2 ( y ) d y = ∫ 0 4 π 1 + 4 tan 2 ( y ) sec 2 ( y ) d y = ∫ 0 4 π 1 + 4 tan 2 ( y ) + 4 tan 4 ( y ) d y = ∫ 0 4 π 1 + 2 tan 2 ( y ) d y = ∫ 0 4 π 2 sec 2 ( y ) − 1 d y = 2 tan ( 4 π ) − 4 π = 2 − 4 π 2 + 4 = 6